Ethical Reasoning in Baccalaureate Nursing Students - Callister, Lynn Clark (Nursing ethics, 2009)
Nurses are encountering an increasing number of ethical dilemmas in clinical practice. Ethics courses for baccalaureate nursing students provide the opportunity for the development of critical thinking skills in order to deal with these effectively. The purpose of this descriptive qualitative study was to describe ethical reasoning in 70 baccalaureate nursing students enrolled in a nursing ethics course. Reflective clinical journals were analyzed as appropriate for qualitative inquiry. The overriding theme emerging from the data was `in the process of becoming', which includes: practicing as a professional, lacking the confidence as a student nurse to take an ethical stand, advocating for patients, being just in the provision of care, identifying the spiritual dimensions of nursing practice, confronting the `real world' of health care, making a commitment to practice with integrity, and caring enough to care. The development of critical thinking and ethical reasoning within the framework of knowing and connecting is essential in nursing education.